Determination of 22 Free Amino Acids in Food for Special Medical Purposes by Ultra-performance Liquid Chromatography - Lili YIN; Hong ZHENG; Zhi CHENG; Lanxiang LU; Xia XUE; Jun WANG; Mei HU; Yanming LIU (Shipin gongye ke-ji, 2023)
A method was established to determine 22 free amino acids in food for special medical purposes by ultra-performance liquid chromatography. After extraction with sulfosalicylic acid and derivation with 2,4-dinitrofluorobenzene (DNFB), the samples were eluted with acetonitrile water-ammonium formate as mobile phase. Amino acids were separated by HSS T3 column and detected with diode-array detector by external standard method. Results showed that, the 22 amino acids were linear in the range of 2~100 µg/mL with correlation coefficients higher than 0.99. The limits of detection (S/N≥3) were 10 mg/100 g, and the limits of quantification (S/N≥10) were 25 mg/100 g. The recoveries were in the range of 90.1% and 109.1% with relative standard deviation (RSD) from 0.8% to 6.9%. This method was simple, efficient, accurate and reproducible. It was suitable for determination of 22 free amino acids in food for special medical purposes, which could provide technical support to ensure the quality and safety.